The Dominance of Music Education in Arts Education Practices in Manado Senior High Schools - Meyltsan Herbert Maragani; Stefanny Mersiany Pandaleke; Rhesti Laila Ulfa; Hartono Hartono; Widodo Widodo (IJCAS (International Journal of Creative and Arts Studies), 2026)
This study aims to analyze the dominance of music education in arts education practices in Manado Senior High Schools. This research employs a qualitative method with a case study approach. The research sites focus on SMA Negeri 1 Manado and SMA Negeri 9 Manado, which demonstrate a strong tendency toward music education practices compared to other art disciplines. Data were collected through in-depth interviews, observations of arts learning activities, and document analysis. The findings suggest that the dominance of music education in the implementation of arts education in senior high schools in Manado is the result of a social construction process formed through three dialectical processes. The first is externalization, in which musical practices emerge from the choices and actions of actors within the school, such as policies supporting choir development, the provision of coaches, and institutional support for musical activities. These practices then undergo objectification as they are positioned as indicators of achievement and as representations of the school, particularly in the arts field. Finally, the process of internalization occurs, in which this constructed reality is accepted by all members of the school community—both teachers and students—as something natural, leading music to be perceived as the primary form of arts education practice in the school. These findings suggest that arts education practices in schools are not entirely neutral; rather, they are influenced by social dynamics, local cultural contexts, and institutional legitimacy that develop within the educational environment.Dominasi Pendidikan Musik dalam Praktik Pendidikan Seni di Sekolah Menengah Atas Kota Manado Abstrak Tujuan penelitian ini adalah menganalisis dominasi pendidikan musik dalam praktik pendidikan seni pada Sekolah Menengah Atas di Kota Manado. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Lokasi penelitian difokuskan pada SMAN 1 Manado dan SMAN 9 Manado yang menunjukkan kecenderungan kuat pada praktik pendidikan musik dibandingkan cabang seni lainnya. Data dikumpulkan dengan wawancara mendalam, observasi pembelajaran seni, serta studi dokumen. Hasil penelitian menunjukkan dominasi pendidikan musik dalam pelaksanaan pendidikan seni pada SMA di kota Manado merupakan hasil dari proses konstruksi sosial yang terbentuk melalui tiga proses dialektis, yaitu eksternalisasi, dimana praktik musikal muncul dari hasil pilihan dan tindakan yang dilakukan para aktor di sekolah seperti kebijakan pengembangan paduan suara, penyediaan pelatih, serta dukungan terhadap kegiatan-kegiatan musikal. Praktik tersebut mengalami objektivasi, melalui pemosisian praktik musikal sebagai indikator prestasi dan representasi sekolah khususnya dalam bidang seni. Kemudian, proses internalisasi, dimana realitas tersebut diterima oleh seluruh warga sekolah, baik guru maupun siswa sebagai sesuatu yang wajar, sehingga musik dipandang sebagai bentuk utama praktik pendidikan seni di sekolah. Hasil temuan ini menunjukkan bahwa praktik pendidikan seni di sekolah pada dasarnya tidak sepenuhnya netral, melainkan dipengaruhi oleh dinamika sosial, budaya lokal, serta legitimasi institusional yang berkembang dalam lingkungan pendidikan.